Higher Education Employability Programmes and Experiences - Glenda Galeotti; Debora Daddi; Oyekunle Oyekunle; Abdallah Al-haddad (Universidade de Lisboa, 2022)
The employability of young graduates has gained increasing importance in the world of work of the 21st century. Higher education (HE) institutions churn out millions of graduates annually to the labour market, but at the same time, employers highlight their lack of requisite skills to sustain employment opportunities. The literature extensively illustrates the relevance of employability programmes in supporting the connection between these two parties throughout the educational process. This paper presents the findings of a comparative analysis on the extent to which HE institutions' employability programmes in Italy, Nigeria, and Palestine promote career development skills in young adults.  The analysis highlights different backgrounds and levels of structuring of the programmes for reducing youth unemployment. Nonetheless, a common trend is observable in the strong synergy with stakeholders in the development and organisation of programmes in order to respond to labour market requirements and students' aspirations.